DISTRIBUTION AND CONSERVATION SIGNIFICANCE OF FEW ENDEMIC AND RARE FISHES WITH REFERENCE TO MEGHALAYA, INDIA - NATH, RUPAK; GOSWAMI, M; SIVA, C.; LASKAR, M. A.; KHARBULI, S. M.; SUMER, S.; KHYRIEM, VANESSA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
The twin drainage systems of Meghalaya, the Brahmaputra and Barak-Surma- Meghna, are rich in Icthyodiversity and also harbour rare and endemic fishes in its large number of hill streams, permanent rivers and tributaries. The present paper portrays distribution of few rare and endemic fishes of twin drainage systems of Meghalaya. Fishes viz., Schistura sijuensis, Glyptothorax striatus and Garra lissorhynchus were recorded from Barak-Surma-Meghna drainage system and Pseudecheneis sulcatus, Pillaia indica were found to be restricted in Brahmaputra drainage. Pethia shalynius, a barb was recorded from both the drainage system. S sijuensis, an endangered and endemic fish species to Meghalaya recorded of Barak-Surma-Meghna drainage. G striatus and P sulcata are Sisorid hill stream cat fish exhibits rare occurrence in Jaiñtia and Khasi hills. Pillaia indica an endangered fish, exhibits restricted distribution in Khasi hills of Brahmaputra drainage. Pethia shalynius is distributed in both the drainage basins Brahmaputra and Barak-Surma Meghna. Distribution of G lissorhynchus commonly known Khasi Garra was found restricted to high gradient zone of streams and rivers of Khasi hills. These species characterized by intrinsic rarity and exhibits high habitat specificity. Both natural and anthropogenic disturbances are responsible to depress the population of fishes of the state and rare species have greater extinction risk than their counterparts. Conservation of habitat must prioritized and anthropogenic disturbances like habitat destruction, pollution, and overexploitation should be controlled, to deaccelerate the momentum of extrinsic rarity of fishes.